ANTIMICROBIAL ACTIVITY OF N-OCTADECANAL ISOLATED FROM THE SEEDS AND PODS OF Acacia nilotica Linn - Garba, S.,; Shoge M.,; Salihu L., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2016)
The antimicrobial activity of n-Octadecanal isolated from A. nilotica was determined using standard methods. The compound was isolated by bioactivity-directed fractionation of ethyl acetate extract of the air dried seeds and pod. The results of the antibacterial screening showed that the ethyl acetate extract of A. nilotica exhibited the highest activities against the test microbes with zones of inhibition diameter ranging from 27-32 mm against Salmonela typhi, Escherichia coli, Streptococcus feacalis, Staphylococcus aureus, Candida krusei and Shigella dysentriae. The structure of the compound was identified from 13Cnmr, 1Hnmr and GC-MS spectral data. The isolation, structural elucidation, NMR spectral assignment and bioactivities are reported.